2014
DOI: 10.1186/1471-2393-14-39
|View full text |Cite
|
Sign up to set email alerts
|

Maternal deaths in eastern Indonesia: 20 years and still walking: an ethnographic study

Abstract: BackgroundThe delays in receiving adequate emergency maternal care described by Thaddeus and Maine twenty years ago are still occurring, as exemplified in this study of cases of maternal deaths in a subdistrict in rural eastern Indonesia.MethodsAn ethnographic design was conducted, recruiting eleven families who reported on cases of maternal deaths in one sub-district of Indonesia, as well as assessing the geographical and cultural context of the villages. Traditional birth attendants and village leaders provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 16 publications
4
30
0
8
Order By: Relevance
“…Tiga kondisi keterlambatan penanganan kegawat daruratan yang sering ditemukan dalam kasus kematian ibu melahirkan adalah keterlambatan dalam pengambilan keputusan sebelum persalinan, keterlambatan dalam mencapai tempat persalinan serta keterlambatan dalam mendapatkan penanganan yang memadai (Ayanian, Markel and Ph, 2016). Beberapa penelitian di Indonesia, menunjukkan bahwa keterlambatan saat persalinan terjadi akibat sulitnya kondisi geografis, terbatasnya ekonomi masyarakat, serta masih tingginya peran dukun dalam proses kehamilan dan persalinan sebagai salah satu aspek sosial budaya yang masih dipertahankan hingga saat ini (Titaley et al, 2010;Birdsall and Hill, 2011;Belton, Myers and Ngana, 2014). Salah satu hambatan dalam mempercepat penurunan AKI di daerah juga terkait dengan kurangnya interaksi ibu hamil dengan lingkungan keluarga dan masyarakat yang lebih luas.…”
Section: Pendahuluanunclassified
“…Tiga kondisi keterlambatan penanganan kegawat daruratan yang sering ditemukan dalam kasus kematian ibu melahirkan adalah keterlambatan dalam pengambilan keputusan sebelum persalinan, keterlambatan dalam mencapai tempat persalinan serta keterlambatan dalam mendapatkan penanganan yang memadai (Ayanian, Markel and Ph, 2016). Beberapa penelitian di Indonesia, menunjukkan bahwa keterlambatan saat persalinan terjadi akibat sulitnya kondisi geografis, terbatasnya ekonomi masyarakat, serta masih tingginya peran dukun dalam proses kehamilan dan persalinan sebagai salah satu aspek sosial budaya yang masih dipertahankan hingga saat ini (Titaley et al, 2010;Birdsall and Hill, 2011;Belton, Myers and Ngana, 2014). Salah satu hambatan dalam mempercepat penurunan AKI di daerah juga terkait dengan kurangnya interaksi ibu hamil dengan lingkungan keluarga dan masyarakat yang lebih luas.…”
Section: Pendahuluanunclassified
“…Nevertheless, an assessment in five regions in Indonesia found that 41.9% of maternal deaths occurred at public hospitals and that Eastern Indonesia and Sulawesi provinces reported the second highest maternal mortality rates and lower levels of service coverage, compared with Java and Bali . Persistent high maternal morbidity and mortality are likely linked to the lack of health workers’ capacity to provide high‐quality care, potentially due to insufficient training, limited experience in managing complications, inadequate infrastructure in which care is provided, and geography . Accordingly, efforts have been focused on improving timely access to care, including effective management of complications during labor at community health facilities ( puskesmas ), and, if necessary, timely and effective referral to a hospital for specialist care…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in Indonesia identified transport as a major barrier to efficient referral; emergency transport was often unavailable and private transport was unreliable and incurred costs. One study identified patients’ and providers’ uncertainty about where to seek emergency care, which resulted in patients traveling to several hospitals before receiving treatment, as a source of delay within an ineffective referral system . A reluctance to admit poorer women covered by social health insurance was also found to be the case in some facilities .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations